Penerapan metode cost plus pricing dalam rangka penetapan harga jual mie mentah pada Bakmi Kriting Glodok - Kasenda, Novelia Deiya Thresia; Alexander, Stanly W.; Pinatik, Sherly (Manajemen Bisnis dan Keuangan Korporat, 2025)
This study definitively examines the application of the cost-plus pricing method in determining the selling price of raw noodles at Bakmi Kriting Glodok. The problem is that the company has always calculated production costs and selling prices using a very simple method. This method does not fully incorporate all production cost elements in accordance with accounting principles. This research employs a qualitative descriptive approach, with data collected through interviews, observations, and documentation of production activities and financial records. The analysis shows that the company has not included all overhead costs, such as equipment depreciation and other factory overheads, in its cost of goods manufactured. This leads to inaccuracies in determining the selling price. The study uses the cost-plus pricing method. This recalculates the production cost and applies a markup to determine a more accurate selling price. The findings show that the selling price determined through the cost-plus pricing method provides a more realistic reflection of production costs and ensures that the business can set competitive prices while maintaining profitability. The results are clear: systematic pricing methods are vital for improving cost control, decision-making and long-term business sustainability.